Kerepek pisang machine - Mustafa, Muhammad Syahmi Anat; Hassan, Mohd Fahrul; Yusup, Muhaimin; Mohamed, Mohd Azren; Abdul Halim, Siti Nur Hasrat; Zakaria, Nur Syuhada (Penerbit UTHM, 2017)
“Kerepek pisang” (Figure 4.1) is one of the most popular snacks among Malaysians from the immemorial time, until now. It was once very popular among the various social groups and ages that includes the rich and the poor, the greatest and the smallest, children and adults, senior citizens, others etc.